2017
DOI: 10.1186/s12889-017-4892-5
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the need for enhanced case management for TB patients as part of TB cohort audit in the North West of England: a descriptive study

Abstract: BackgroundPatients with TB have diverse and often challenging clinical and social needs that may hamper successful treatment outcomes. Understanding the need for additional support during treatment (enhanced case management, or ECM) is important for workforce capacity planning. North West England TB Cohort Audit (TBCA) has introduced a 4-level ECM classification system (ECM 0–3) to quantify the need for ECM in the region. This study describes the data from the first 2 years of ECM classification.MethodsData co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…6.7 Our previous research from North West England has shown that patients with higher ECM levels are more likely to have adverse TB treatment outcomes, despite the mitigating effects of enhanced TB care. 4 Our new findings suggest that not only may TBCA and ECM be vital in identifying patients who require additional support to achieve TB treatment success, but that these can also be used to indirectly estimate the needs of the close contacts of these patients. This is important because contact tracing and provision of preventive therapy are well-established, important tools in TB prevention, and enhanced support is required not only for high-risk TB patients but also for their households.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…6.7 Our previous research from North West England has shown that patients with higher ECM levels are more likely to have adverse TB treatment outcomes, despite the mitigating effects of enhanced TB care. 4 Our new findings suggest that not only may TBCA and ECM be vital in identifying patients who require additional support to achieve TB treatment success, but that these can also be used to indirectly estimate the needs of the close contacts of these patients. This is important because contact tracing and provision of preventive therapy are well-established, important tools in TB prevention, and enhanced support is required not only for high-risk TB patients but also for their households.…”
Section: Discussionmentioning
confidence: 84%
“…3 In North West England, TB specialist nurses evaluate the clinical and social needs of TB patients and assign an ECM level from 0 (standard case management) to 3 (complex needs requiring the highest level of intensive support), which is subse-quently reassessed during multidisciplinary TB cohort review (known as TB cohort audit [TBCA] in North West England). 4 The ECM offered varies according to the needs of each household, but can include intensive support from ancillary services and partner organisations, more frequent clinic or home visits, and transport vouchers or translation services to overcome language barriers. Table 1 provides a summary of the guide to the classification of patients to ECM levels used in TB cohort reviews.…”
Section: O N C L U S I O N Smentioning
confidence: 99%
“…This is in agreement with the notion that TLR primarily modulate the early steps of innate immunity. To identify whether the transcriptome changes induced by CpG‐B reflected the differential accumulation of specific cell types in dLN, we analyzed these data using xCell, a deconvolution software to infer cell subsets abundance from transcriptomes [ 6 ]. This in silico analysis suggested that EAE induction was associated with an accumulation of neutrophils in dLN on day 3 p.i.…”
Section: Resultsmentioning
confidence: 99%